2014
DOI: 10.3329/seajph.v3i2.20034
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and vaccination status of hepatitis B amongst medical interns of Rural Medical College, Loni, Maharashtra, India

Abstract: Hepatitis B Virus (HBV) infection is a serious global public health problem. It is the most common blood borne viral infection which places healthcare professional at higher occupational risk. The present study was conducted to assess the current knowledge and vaccination status about hepatitis B amongst medical interns. A cross-sectional study was conducted between February and March 2009 on 100 medical interns of the Rural Medical College, Loni, India. A pre-designed questionnaire which assessed their knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
(7 reference statements)
2
5
3
1
Order By: Relevance
“…In 2002, a better vaccination coverage (63.5%) was reported among dentists of the private dental sector in Riyadh (Al-Rabeah and Mohamed, 2002). The majority (88.9%) of the participants in the present study received HB vaccination, which is equal or higher than the rates reported from recent studies in Saudi Arabia (Al-Dharrab and Al-Samadani, 2012; Alqahtani et al, 2014; Al-Hazmi, 2015) and other countries (Adekanle et al, 2015; Giri and Phalke, 2013; McCarthy and MacDonald, 1997; Osman et al, 2015). The high rate of HB vaccine utilisation can be explained by being mandatory for all healthcare workers, available in all institutions and provided free of charge.…”
Section: Discussioncontrasting
confidence: 57%
“…In 2002, a better vaccination coverage (63.5%) was reported among dentists of the private dental sector in Riyadh (Al-Rabeah and Mohamed, 2002). The majority (88.9%) of the participants in the present study received HB vaccination, which is equal or higher than the rates reported from recent studies in Saudi Arabia (Al-Dharrab and Al-Samadani, 2012; Alqahtani et al, 2014; Al-Hazmi, 2015) and other countries (Adekanle et al, 2015; Giri and Phalke, 2013; McCarthy and MacDonald, 1997; Osman et al, 2015). The high rate of HB vaccine utilisation can be explained by being mandatory for all healthcare workers, available in all institutions and provided free of charge.…”
Section: Discussioncontrasting
confidence: 57%
“…It can therefore be said that their knowledge was relatively lower when compared to participants from other studies conducted on medical students by Singh et al (86.7% had correct knowledge), Giri and Phalke (90% had correct knowledge) and Magdey et al (77.7% had correct knowledge). 13,14,17 However, Khan et al's study showed similar level of knowledge (57.1%) among medical students as that shown by present study. 18 Doctors/health worker was the most common source of information among all academic batches with media being the 2nd choice.…”
Section: Discussionsupporting
confidence: 38%
“…Similar results were observed by studies conducted by Singh and Jain and Giri and Phalke on medical students. 13,14 Statistically Significant difference (p<0.001) was witnessed in their vaccination status. Only 18.97% of 1st year students reported being vaccinated for HBV when compared to 2nd (98.18%), 3rd (94%) and 4th (100%) year students.…”
Section: Discussionmentioning
confidence: 99%
“…This underscores the need for them to have adequate knowledge regarding the disease because it is assumed that adequate knowledge of the disease will in turn influence their attitude toward the disease and subsequently impact their vaccination status. Scholars observed that in relation to the disease, there exists a gap between knowledge and practice because many healthcare workers are still not immunized against hepatitis B [7]. Again, a study conducted among medical and health science students established that 4.7% of the study participants completed all three doses of their vaccination schedule; 8.7% students were incompletely vaccinated.…”
Section: Introductionmentioning
confidence: 99%